(3GSJQGJjLjGJ JfehjI eJbOeIs - (3JQ(B.(3eNjeQ eMeO Gejf(B, s ((3GdYjf(B:s (3OGQ GdcfGH GdLGeYj(B,s, 2009)
(3GJLGgGJ h bVGjG YGdejI fMh GbJUGOjGJ GdeYQaI , GdGWGQ GdJMdjd h YfGUQ GdJejR aj GbJUGO GdeYQaI , YedjGJ HfGA GbJUGO eYQaj , JMSjf GdefXheI GdGbJUGOjI h GdeDSSjI , JYRjR GdGHJcGQ h GdHfjI GdJMJjI ddHMK h GdJcfhdhLjG , JYRjR GdHfjI GdJMJjI dbWGY GdeYdheGJ h GdGJUGdGJ , GdEQJbGA HGdJYdje GdCSGSSj , GdKGdKj h GdJYde eOi GdMjGI , GdJhLjgGJ GdGSJQGJjLjI dYOOef GdOhd h GdJcJdGJ eKd GdUjf h GdgfOs
(3eQGLY U(B.333 (3;edGMb U(B.311s
Keywords: (3GdGbJUGOs; (3GdeYQaIs